Ethics of Islamic Economics (Scientific and Research Review on the Importance of Religious and Ethical Values in Trade and Economy) - Bakht Shaid; Hafiz Muhammad Sani (Journal of Islamic and Religious Studies, 2018)
Islam is a holistic and comprehensive system of life because the Creator of universe has given the instructions that are eternal and are perfect guide for humanity in all ages and circumstances. Islamic teachings are consistent with the comprehensive nature. Those instructions that human being has given for all walks of life in that the elements of morality is distinct and dominant and prohibited every act that is harmful to others. This fact is quite clear that the moral aspect of Islam is so important to consider the ethics of Islam has taken into consideration and there is no command to be out of the realm of ethics and particularly matters of life which is part of religion and are important aspect of society. Islamic teachings are so clear that there is no example of it in any economic system the world. Today we have different economic systems in the world which essentially teach us that the purpose of human life is to make money and collect goods even if affects the lives of others. But in Islamic economic world it is emphasized that this world is not the original house and satisfactory zone of human being and his purpose is not to collect wealth but the worship of Almighty. Human being is gifted fair system of order in every aspect of which there is clearly ethics thus human is strictly prohibited to collect money through unfair means and in cruel manners. In this article we will discuss the ethical consideration of Islamic economical system.So it is quite clear that the guarantor of peace, love and harmony in the world is Islamic system.